Divided Loyalties : Young Somali Americans and the Lure of Extremism - Weber, Joseph (Professor of journalism) (Book collections on Project MUSE., 2020)
"The book is about the 2016 trial in Minneapolis of several Somali immigrant and Somali American men for trying to join ISIS. It examines the process of radicalization and the reasons why one of the young men chose to cooperate with the FBI and testify against his friends and family members"--